Africa's threatened livestock breeds - International Livestock Research Institute (International Livestock Research Institute, 2012)
Resilient, disease-resistant,'ancient' cattle are among the African breeds at risk of extinction as imported animals supplant valuable native livestock on the continent. Urgent action is needed to stop the rapid and alarming loss of genetic diversity of livestock in Africa and throughout the developing world. In this photofilm, Okeyo Mwai, a scientist at the International Livestock Research Institute (ILRI),explains the value of conserving Africa's threatened livestock breeds.